Ethnic and religious factor in the development of Ukrainian regions: socio-geographical analysis - Ivan Kostaschuk; Petro Mruchkovskyi (Kazimierz Wielki University, 2018)
The article studies the influence of ethnic and religious factors on the formation of ethnic and confessional structure of Ukrainian regions, and it distinguishes the commonality between the ethnic structure of the population of the region and its level of confessionality. On the basis of selected research methods, the classification of Ukrainian regions according to the degree of ethnic structure of the population and the number of registered communities has been conducted. As a result of the conducted research, the religious-geographical zoning of the territory of Ukraine was conducted which takes into account the ethno-geographical features of the development of the regions.